2018
DOI: 10.1111/cdoe.12416
|View full text |Cite
|
Sign up to set email alerts
|

Oral health‐related quality of life as a predictor of subjective well‐being among older adults—A decade‐long longitudinal cohort study

Abstract: OHRQoL seems to be a substantial predictor of subjective well-being in quinquagenarians and septuagenarians across the rather long observational period. Further studies with larger sample sizes are required to confirm this finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…Previous studies have shown subjective health and quality of life outcomes among older population and people living with disease conditions (Bishwajit et al 2017;Klotz et al 2018;Matsuguma et al 2018;Calys-Tagoe et al 2014;Ryan et al 2007). Currently, there are no other studies showing the predictors of subjective health, happiness, and life satisfaction among healthy adolescent populations in an African context.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown subjective health and quality of life outcomes among older population and people living with disease conditions (Bishwajit et al 2017;Klotz et al 2018;Matsuguma et al 2018;Calys-Tagoe et al 2014;Ryan et al 2007). Currently, there are no other studies showing the predictors of subjective health, happiness, and life satisfaction among healthy adolescent populations in an African context.…”
Section: Discussionmentioning
confidence: 99%
“…Especially to individuals aged 85 years and older, when changes in the life situation is likely to occur, studies of social and health-related changes in relation to changes in morale is of high relevance. Thus far, only a few studies (Klotz et al 2018;Näsman et al 2019;Scott and Butler 1997) have focused on decreasing morale and associated factors longitudinally. One of the studies focused on very old age, and included a sample with a mean age of 87 years at baseline (Näsman et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Further, the results showed that the two older age groups (90-year-olds and ≥ 95-year-olds) had a significantly higher score in the index of negative life events compared to the 85-year-olds, indicating that the risk of experiencing negative life events increased in advanced age. Another recent study focused on individuals in their fifties and in their seventies, and showed that worse oral health-related quality of life predicted lower morale over 10 years in both age cohorts (Klotz et al 2018). A third study included individuals with a mean age of 71 at baseline (Scott and Butler 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The concept of the OHQoL-UK(W) scale is based on assumption that oral health affects quality of life, and it was indeed shown in studies where large proportion of respondents perceived oral health as important predictor of their quality of life 13 . Positive influence of good oral health on quality of life is especially present in younger, more educated persons who more frequently visit their dentists 14,15 .…”
Section: Discussionmentioning
confidence: 99%